Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Ein Beitrag zur Verarbeitung von Dickblech aus utlrahochfesten Stahlwerkstoffen - Rostek, Tim
Die Fertigung von innovativen Bauteilen aus ultrahochfesten Stählen erfordert oft Wärmebehandlungen zur Einstellung höchster mechanischer Festigkeiten. Bei Einsatz dickwandiger Halbzeuge mit entsprechend hoher Wärmekapazität eignen sich konventionelle Wärmebehandlungstechnologien und -prozessführungen jedoch nur eingeschränkt für einen effizienten Herstellungsprozess. Inhalt dieser Arbeit sind daher innovative Fertigungsstrategien, welche die wirtschaftliche Herstellung entsprechender Bauteile vor dem Hintergrund einer effektiven Formgebung sowie einer anforderungsangepassten Werkstoffbehandlung zum Ziel haben. Spezielle Temperaturführungsstrategien als auch thermomechanische Herangehensweisen zum Einstellen besonders günstiger mechanischer Eigenschaften entsprechender Stahlwerkstoffe stellen in diesem Kontext vielversprechende Ansatzpunkte dar.

Hans Werner Henze und seine Zeit - Tumat, Antje (Musiktheorie)

Monolithic on-chip integration of semiconductor waveguides, beamsplitters and single-photon sources - Jöns, Klaus D.; U. Rengstl, U; Ostermann, M; Hargart, F; Heldmaier, M; Bounouar, S; Ulrich, S.M; Jetter, M; Michler, P

Earenfight, Theresa: Queenship in Medieval Europe - Foerster, Anne (Das Mittelalter)

Einfluss von Werkstoff, Prozessführung und Wärmebehandlung auf das bruchmechanische Verhalten von Laserstrahlschmelzbauteilen - Riemer, Andre

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (International Colloquium on Automata, Languages, and Programming (ICALP 2015))
The study of ground state energies of local Hamiltonians has played a fundamental role in quantum complexity theory. In this paper, we take a new direction by introducing the physically motivated notion of ``ground state connectivity'' of local Hamiltonians, which captures problems in areas ranging from quantum stabilizer codes to quantum memories. We show that determining how ``connected'' the ground space of a local Hamiltonian is can range from QCMA-complete to PSPACE-complete, as well as NEXP-complete for an appropriately defined ``succinct'' version of the problem. As a result, we obtain a natural QCMA-complete problem, a goal which has generally proven difficult since the conception of QCMA over a decade ago. Our proofs rely on a new technical tool, the Traversal Lemma, which analyzes the Hilbert space a local unitary evolution must traverse under certain conditions. We show that this lemma is essentially tight with respect to the length of the unitary evolution in question.

Quantum Hamiltonian Complexity - Gharibian, Sevag; Huang, Yichen; Landau, Zeph; Woo Shin, Seung (Foundations and Trends® in Theoretical Computer Science)
Constraint satisfaction problems are a central pillar of modern computational complexity theory. This survey provides an introduction to the rapidly growing field of Quantum Hamiltonian Complexity, which includes the study of quantum constraint satisfaction problems. Over the past decade and a half, this field has witnessed fundamental breakthroughs, ranging from the establishment of a “Quantum Cook-Levin Theorem” to deep insights into the structure of 1D low-temperature quantum systems via so-called area laws. Our aim here is to provide a computer science-oriented introduction to the subject in order to help bridge the language barrier between computer scientists and physicists in the field. As such, we include the following in this survey: (1) The motivations and history of the field, (2) a glossary of condensed matter physics terms explained in computer-science friendly language, (3) overviews of central ideas from condensed matter physics, such as indistinguishable particles, mean field theory, tensor networks, and area laws, and (4) brief expositions of selected computer science-based results in the area. For example, as part of the latter, we provide a novel information theoretic presentation of Bravyi’s polynomial time algorithm for Quantum 2-SAT.

Tensor network non-zero testing - Gharibian, Sevag; Landau, Zeph; Woo Shin, Seung; Wang, Guoming (Quantum Information & Computation)
Tensor networks are a central tool in condensed matter physics. In this paper, we initiate the study of tensor network non-zero testing (TNZ): Given a tensor network T, does T represent a non-zero vector? We show that TNZ is not in the Polynomial-Time Hierarchy unless the hierarchy collapses. We next show (among other results) that the special cases of TNZ on non-negative and injective tensor networks are in NP. Using this, we make a simple observation: The commuting variant of the MA-complete stoquastic k-SAT problem on D-dimensional qudits is in NP for logarithmic k and constant D. This reveals the first class of quantum Hamiltonians whose commuting variant is known to be in NP for all (1) logarithmic k, (2) constant D, and (3) for arbitrary interaction graphs.

Entwicklung einer Kennwertprognose für mit Blindnietelementen elementar gefügte CFK- Mischbauverbindungen auf Basis von experimentellen Untersuchungen - Hessing , Florian